The ‘Curse of the Law’ and the Inclusion of the Gentiles: Galatians 3. 13–14 - Donaldson, T. L. (New Testament studies, 1986)
The path of Paul's argumentation in Gal 3. 1–4. 7 presents vexing problems for any who would attempt to retrace it. The terminal points are clear: he begins with ‘Christ … crucified’ (3. 1; cf. 2. 21) and ends with the inclusion of the uncircumcized Gentile believers among the true ‘seed’ of Abraham (3. 26–29; 4. 7). But the route by which he moves from ‘cross’ to ‘Gentiles’–a maze of laboured exegesis, puzzling illustration, and cryptic theological shorthand–is anything but clear.